ответ:1) (5а+3)+(-3а-4)=5а+3-3а-4=2а-1
(5а+ 3)-(-3а-4)=5а+3+3а+4=8а+7
2) (7х2+3х)+(-2х-1)=7х2+3х-2х-1=7х2+ 1х-1
(7х2+3х)-(-2х-1)= 7х2+3х+2х+1=7х2+ 5х+1
3)( 8b2 + 2b - 4)+( 5 - 3b - 9b2)= 8b2 + 2b – 4+5 - 3b - 9b2=-b2-b+1
( 8b2 + 2b - 4)-( 5 - 3b - 9b2)= 8b2 + 2b – 4 -5+3b+9b2=17b2+ 5b-9
4) (11y - 12 - y3)+( 14 - 12y + y3)= 11y - 12 - y3+14 - 12y + y3=-y+y3+2
(11y - 12 - y3)-( 14 - 12y + y3)= 11y - 12 - y3-14+12y-y3=23y-2y3-26
5) (6 + mn + 2)+( 4 - mn - m2)= 6 + mn + 2+4 - mn - m2=12-mn-m2
(6 + mn + 2)-( 4 - mn - m2)= 6 + mn + 2-4+mn+m2=4+2mn+m2
Объяснение:
не благодарите
Поделитесь своими знаниями, ответьте на вопрос:
Найдите значения выражения 2 ) - 4a^2b^2c^2* 6 a^4c^3 при а=1, , b=1/4 , c=24 ) - 25n^2m^2*0, 16n^5m^7 при n= -0, 1, m=10
- 4a^2b^2c^2* 6 a^4c^3 =-24a^6b^2c^5=-24(1)^6(1/4)^2(2)^5=
=-(24/16)·32=-48
4) - 25n^2m^2*0,16n^5m^7 при n= -0,1, m=10
- 25n^2m^2*0,16n^5m^7=- 25*0,16n^7m^9=- 25*0,16*(-0,1)^7*(10)^9=
=25*16=400